2014
DOI: 10.1371/journal.pone.0108132
|View full text |Cite
|
Sign up to set email alerts
|

Serum Complement C3f and Fibrinopeptide A Are Potential Novel Diagnostic Biomarkers for Non-Alcoholic Fatty Liver Disease: A Study in Qingdao Twins

Abstract: AimsTo compare the different serum peptidome patterns between twins with and without non-alcoholic fatty liver disease (NAFLD) in order to help understand the pathogenesis of NAFLD and to identify potential diagnostic and therapeutic targets.MethodsThe peptidomics patterns of 63 cases with NAFLD were compared with their twin healthy controls in Qingdao, China. Peptides between 800Da and 3500Da were captured and concentrated using C18 reversed-phase columns, followed by MALDI-TOF mass spectrometry. The sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Systemic activation of complement through the alternative pathway has been demonstrated in liver biopsies of NAFLD patients [22,23] and associated with an increase in circulating levels of its cleavage product C3a [38]. Similarly, a peptidomic study involving patients with NAFLD and twin controls demonstrated significantly higher levels of C3f [39]. Moreover, two large clinical studies confirmed the association between C3 levels and NAFLD [24,25] independently of other metabolic features.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Systemic activation of complement through the alternative pathway has been demonstrated in liver biopsies of NAFLD patients [22,23] and associated with an increase in circulating levels of its cleavage product C3a [38]. Similarly, a peptidomic study involving patients with NAFLD and twin controls demonstrated significantly higher levels of C3f [39]. Moreover, two large clinical studies confirmed the association between C3 levels and NAFLD [24,25] independently of other metabolic features.…”
Section: Discussionmentioning
confidence: 87%
“…However, the relationship between NAFLD and obesity is already well-established in the literature [9]. Similarly, a peptidomic study involving patients with NAFLD and twin controls demonstrated significantly higher levels of C3f [39]. Complement proteins are synthesized mainly in the liver but visceral adipose tissue contributes significantly to C3 levels during obesity and other dysmetabolic or inflammatory states.…”
Section: Discussionmentioning
confidence: 96%
“…The role of complement in liver diseases is less well characterized. The complement components C3 and C5 were reported to be associated with NAFLD [39][40][41] and C5 had a causal role in liver fibrogenesis [42]. There are strong and persistent stimuli for complement activation in NAFLD through multiple pathways, including the classical pathway and the lectin pathway [43], as well as the alternative pathway [44].…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis is the main pathological basis of the ischemic cardiocerebrovascular diseases. Although the pathogenesis of atherosclerosis is not well defined, more and more evidence from the find that the high level of FPA in blood means activation of the coagulation system (Ekwere, Ebele, Ekanem, & Ogunro, 2014;Omarov, Sultanov, & Ragimov, 2012) and occurs in the patients with venous thrombosis, pulmonary embolism, and ischemic heart disease as a biomarker (Gianazza et al, 2010;Morris et al, 2003;Xin et al, 2014). However, to date, little is known about the pathological effects of FPA in the cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%